Effect of non-enzymatic glycosylation in the epigenetics of cancer. (August 2022) - Rehman, Shahnawaz; Aatif, Mohammad; Rafi, Zeeshan; Khan, Mohd Yasir; Shahab, Uzma; Ahmad, Saheem; Farhan, Mohd
Abstract: The non-enzymatic glycosylation or non-enzymatic covalent modifications (NECMs) or glycation of cellular proteins result in the generation and accumulation of advanced glycation end products (AGEs) that are associated with the epigenetics of cancer. Epigenetic modifications are inheritable changes without alterations in the sequences of DNA. Glycation-mediated epigenetic mechanisms change the accessibility of transcriptional factors to DNA via rearrangement or modification in the chromatin structure and collaborate with gene regulation in the pathogenesis of cancer. Epigenetic mechanisms play a critical role in sustaining the tissue-specific gene expression. Distraction from normal epigenetic mechanism results in alteration of gene function, initiation and progression of cancer, and cellular malignant transformation. Epigenetic modifications on DNA and histones control enzymatic expressions of corresponding metabolic pathways, which in turn influence epigenetic regulation. Glycation of histones due to persistent hyperglycemia results in histone-histone and histone-DNA cross-linking in chromatin by compromising the electrostatic interactions, that affect the dynamic architecture of chromatin. Histone proteins are highly prone to glycation due to their basic nature and long half-lives, but the exact role of histone glycation in the epigenetics of cancer is still in the veil. However, recent studies have suggested the role of histone glycation mediated epigenetic modifications that affect cellular functioning by altering the gene expressions of related metabolic pathways. Moreover, dicarbonyls-induced NECMs of histones perturb the architecture of chromatin and transcription of genes via multiple mechanisms. Contrary to the genetic causes of cancer, a possible reversal of glycation-mediated epigenetic modifications might open a new realm for therapeutic interventions. In this review, we have portrayed a mechanistic link between histone glycation and cancer epigenetics.